Delivering innovative involvement through data engagement infrastructure: the Northern Ireland Public Data Panel - Nelson, Elizabeth; Burns, Frances; Wilson, John (International Journal of Population Data Science, 2025)
Objectives The Northern Ireland Public Data Panel (NIPDP) facilitates public deliberation on the use of public data across the data ecosystem. Co-created by its members and a team from ADRC NI and the Data Institute, NIPDP develops and tests best practice in involvement and democratic deliberation on data-driven issues. Methods NIPDP was developed and implemented as data engagement infrastructure with support from across the data ecosystem, recognising the interplay of data and its uses beyond academic research. Recruitment was carried out by citizen assembly recruitment specialists Sortition to be broadly representative of the NI population. Seventeen members, supported by the NIPDP delivery team, meet quarterly to hear expert evidence and deliberate on a topic selected by members through an open application process. Recommendations are recorded and connected into stakeholders and decision-makers through the All-Party Group on Policy and Public Data and through ADRC NI and the Data Institute. Results NIPDP has developed a successful approach to meaningful involvement of diverse publics in data-driven decision-making across a geographic region. It differs in other approaches to engagement and involvement in data-driven research and decision-making in three distinct ways: 1) it encompasses the entire data ecosystem; 2) its recruitment was designed to be as representative as possible across a geographic area; 3) it is co-created with its members. This paper will discuss NIPDP’s approach from development to formal establishment, including some considerations from two Data Dialogues, the deliberation events on data topics with members. It will offer some learning regarding a partnership model for delivery of data engagement infrastructure, democratic deliberation in data-driven issues, co-creation in the data ecosystem, and ensuring involvement is meaningful and linked to decision-making. Conclusion NIPDP demonstrates the potential for bespoke data engagement infrastructure to involve diverse publics in data-driven decision-making. It offers learning for other initiatives around partnership delivery, co-creation of engagement infrastructure and public deliberation.